Relevance of maxilofacial anatomy in endodontics: A review - Somayaji Krishnaraj S.; Rao Mohandas K.G. (Acta Stomatologica Naissi, 2012)
A thorough anatomical knowledge is very essential for any surgical procedure. The idea of location of various structures in the body prepares the clinician for a better approach to establishing diagnosis and various surgical procedures. Unfortunately, anatomical variations can lead to hazards in diagnosis and treatment. Referred pain and pain of unknown origin or temporomandibular joint pain sometimes may lead to confusion or misinterpretation in proper diagnosis. Abnormal course and distribution of nerves and vessels may sometimes become a major problem. There may be an overlapping of the nerves of the two sides supplying the teeth or some of the nerves may be duplicated in the whole or part of their course. Such conditions may lead to problems in anesthetizing teeth or unexpected pain sensations expressed by the patient during the endodontic treatments. Anatomical relation of maxillary air sinus to the upper teeth and the possible clinical complications during the treatment is also important. Relation of neurovascular bundle to the sinus may sometimes vary. Lack of knowledge of normal anatomy may lead to misinterpretation of tests leading to wrong diagnosis and management. Concept of anatomical variations is of utmost importance to prevent complications of anesthetic procedures.